TRANSFORMATION OF SMES IN WEST JAVA: BUILDING NATIONAL ECONOMIC RESILIENCE THROUGH DIGITAL INNOVATION - Evi Mafriningsianti; Sandi Setiadi (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the effect of digital transformation, MSME innovation, and government policies on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in West Java, with Human Resource (HR) capacity as a moderating variable. Using a quantitative approach with a causal design, this study tests hypotheses through Structural Equation Modeling (SEM) with the help of SmartPLS software. The research population consists of active MSMEs in West Java Province, with a minimum sample of 99 respondents selected using stratified purposive sampling. The results show that digital transformation has a positive and significant effect on MSME sustainability. MSME innovation also shows a very strong and dominant positive effect on business sustainability. In addition, government policies also contribute positively and significantly to the sustainability of MSMEs, although the impact is relatively weaker. However, an important finding is that human resource capacity does not significantly moderate the relationship between digital transformation, innovation, and government policies on the sustainability of MSMEs. This is likely due to the low digital literacy of MSME human resources or because the innovations carried out are still simple and do not require high human resource skills.